Language as Ideology: A Study of Absurd Theatre (The International Journal of Educational Sciences and Arts, 2025)
The study introduces absurdity to the reader and shows the emergence of Absurd Theatre. The research also gives definitions and explanations for the terms “Ideology”, “Linguistic Manipulation”, and “Power Dynamics”. This paper explores and reveals language ideology, cultural values, as well as power relations in Ionesco’s The Lesson. It provides references to the theoretical background of absurdity in pairing with linguistic manipulation. It epitomizes that the conspicuous aspects of the use of language to convey the power dynamics are anchored on absurdity which is the topic of Eugene Ionesco’s play The Lesson. It also gives evidence to the belief that examination of linguistic absurdity ideas is fully applicable to the Ionesco’s The Lesson.
Keywords: English Language; Ideology; Absurd Theatre